If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 6r + -3 = 7r + 8 + -3r Reorder the terms: 5 + -3 + 6r = 7r + 8 + -3r Combine like terms: 5 + -3 = 2 2 + 6r = 7r + 8 + -3r Reorder the terms: 2 + 6r = 8 + 7r + -3r Combine like terms: 7r + -3r = 4r 2 + 6r = 8 + 4r Solving 2 + 6r = 8 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 2 + 6r + -4r = 8 + 4r + -4r Combine like terms: 6r + -4r = 2r 2 + 2r = 8 + 4r + -4r Combine like terms: 4r + -4r = 0 2 + 2r = 8 + 0 2 + 2r = 8 Add '-2' to each side of the equation. 2 + -2 + 2r = 8 + -2 Combine like terms: 2 + -2 = 0 0 + 2r = 8 + -2 2r = 8 + -2 Combine like terms: 8 + -2 = 6 2r = 6 Divide each side by '2'. r = 3 Simplifying r = 3
| 3(y-7)-8y=4 | | 7y+4=8y | | 0.02/0.7 | | 7(x-9)+6(4x-7)=30(x-4)-3 | | g=3h+5 | | g=4h+1 | | 5.6(4+4x)-9.4=13 | | 4(u+2)-7u=17 | | 0.7/0.02 | | 5/6-(1/18) | | 5.3=x(x+.6)(x-.1) | | 5/8-(1/8) | | 1/5x-3/8y=12 | | 4y+1-2y=3+y+9 | | -4w-2/3=7/5w-4/5 | | -8(n+8)=2-7n | | -10a+40=9 | | X(t)=1-u(t-3)+(t*u(t-3)) | | 8/9x=8+4/9 | | 12a^3/5a | | 6t^2-36t+48= | | 55-8x= | | (X-5)+X=82 | | 3u-25=2u | | 5w+7-2=5+4 | | (X+5)+x=82 | | 12x-22/132 | | 5r^2+6r-1=0 | | x^4-4x^3-24x^2+40x+100=0 | | Graphy=2.5+0.075x | | 9ln(8x)=18 | | 5x+36y-z=0 |